2023
DOI: 10.3390/pharmaceutics15030884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Parameters, Protectants and Carrier Materials on the Survival of Yeast Cells during Fluidized Bed Granulation for Tableting

Abstract: The administration of living microorganisms is of special interest, with regard to probiotic microorganisms providing health benefits to the patient. Effective dosage forms require the preservation of microbial viability until administration. Storage stability can be improved by drying, and the tablet is an especially attractive final solid dosage form due to its ease of administration and its good patient compliance. In this study, drying of the yeast Saccharomyces cerevisiae via fluidized bed spray granulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…As preservatives, starch, lactose, inulin, dextran, sorbitol, trihalose, two different ratios of milk powder, maltrodextrin, xylose and two different ratios of trihalose + milk powder mixture were compared, respectively. It was observed that trihalose + milk powder mixture used in equal proportions had a significant effect on bacterial viability compared to tablets without preservatives (89). The same research group examined the parameters in the tablet pressing process of the granules of S. cerevisiae formed by spray drying technique.…”
Section: Different Approaches To Oral Pharmabiotic Tabletsmentioning
confidence: 99%
“…As preservatives, starch, lactose, inulin, dextran, sorbitol, trihalose, two different ratios of milk powder, maltrodextrin, xylose and two different ratios of trihalose + milk powder mixture were compared, respectively. It was observed that trihalose + milk powder mixture used in equal proportions had a significant effect on bacterial viability compared to tablets without preservatives (89). The same research group examined the parameters in the tablet pressing process of the granules of S. cerevisiae formed by spray drying technique.…”
Section: Different Approaches To Oral Pharmabiotic Tabletsmentioning
confidence: 99%
“…The data analysis resulted in an optimal operating point at a loading rate of 350 kg/h and temperatures between 29 and 33 • C as well as high yeast cell viability of up to 76%, which was 27% higher than the viability of the yeast in the normal operating conditions of the plant. According to Vorländer et al [79], fluidized bed application enables faster drying than lyophilization, on the one hand, and lower temperatures than spraydrying, on the other hand, the two predominantly used techniques for life-sustaining drying of microorganisms. In this study, the authors showed different protectants for S. cerevisiae, such as mono-, di-, oligo-and polysaccharides, but also skimmed milk powder and one alditol, as they, or chemically similar molecules, are known from other drying technologies to stabilize biological structures such as cell membranes, and thus, improve survival during dehydration.…”
Section: Fluidized Bed Dryingmentioning
confidence: 99%
“…According to Wirunpan et al [84], the survival rate of L. lactis 1464 in shrimp feed pellets ranges from 89.54% to 96.87% at 80 and 50 • C, respectively. The survival rate in the fluidized bed drying process is intrinsically related to process temperature, drying time, and cell concentration [79]. Wu et al [85] evaluated the optimization of the process parameters using a fluidized bed to dry and encapsulate L. brevis RK03; the authors achieved a survival rate of 95% using casein and whey protein as carriers.…”
Section: Fluidized Bed Dryingmentioning
confidence: 99%
“…Conduct stability testing to assess the viability of probiotic strains throughout the product's shelf life. Assess the influence of temperature, humidity, and other environmental factors on probiotic viability to select the most suitable strain for the design [12].…”
Section: Probiotic Strainmentioning
confidence: 99%
“…Conversely, consolidation time did not exert a significant impact on the tablet quality attributes considered. Given the negligible changes in survival rates relative to tensile strength (due to opposing yet compensatory influences on porosity), high production speeds could be employed for granule tabletting without compromising viability, as long as tablets with equivalent tensile strength are produced [28,29].…”
Section: Influence Of Compression Kinetics During Tabletingmentioning
confidence: 99%